2021
DOI: 10.1098/rspb.2021.1604
|View full text |Cite
|
Sign up to set email alerts
|

A sink host allows a specialist herbivore to persist in a seasonal source

Abstract: In seasonal environments, sinks that are more persistent than sources may serve as temporal stepping stones for specialists. However, this possibility has to our knowledge, not been demonstrated to date, as such environments are thought to select for generalists, and the role of sinks, both in the field and in the laboratory, is difficult to document. Here, we used laboratory experiments to show that herbivorous arthropods associated with seasonally absent main (source) habitats can endure on a suboptimal (sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…However, it is crucial to recognize whether the mite has the potential to feed on other plant resources because wheat only serves as a temporary resource for the mites due to seasonal fluctuations. Recent research has shown that other plant species can serve as temporary reservoirs (stepping stones) for the mite (Laska et al, 2021 ), although no study to date has considered whether and how environmental heterogeneity can affect the mite pest potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is crucial to recognize whether the mite has the potential to feed on other plant resources because wheat only serves as a temporary resource for the mites due to seasonal fluctuations. Recent research has shown that other plant species can serve as temporary reservoirs (stepping stones) for the mite (Laska et al, 2021 ), although no study to date has considered whether and how environmental heterogeneity can affect the mite pest potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not yet been confirmed for A. tosichella . Therefore, in fluctuating agricultural environments, the subsistence of A. tosichella populations most likely depends on their potential to use different plant resources, some of them being sink habitats that function as temporary stepping stones (Laska et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is becoming increasingly clear that, if you look close enough, no system is simple. Indeed, the genetic basis of pesticide resistance is more complex than previously thought (Ffrench‐Constant, 2013 ; Labbé et al, 2007 ), adaptation to host plants do not follow simple rules even in simple systems (Laska et al, 2021 ; Magalhães et al, 2014 ), and trophic interactions are not always organized into a trophic chain, even in agroecosystems (Rosenheim, 1998 ; Rosenheim et al, 1995 ; Van Rijn et al, 2002 ). Moreover, agricultural landscapes are changing, with the general understanding that relying on pesticides and monocultures is not only environmentally detrimental, but also not optimal for pest control and plant yield in the long term (Janssen & van Rijn, 2021 ).…”
mentioning
confidence: 99%